Pengaruh Ekspektasi Pendapatan, Lingkungan Keluarga Dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha (Studi Pada Mahasiswa FEB Universitas Muhammadiyah Metro) - Febriyanto; Nani Septiana; Yulia Ardianti (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aimed at determining and analyzing the effects of income expectations, family environment and entrepreneurship education on entrepreneurial intentions (study on the students of the Economics and Business Faculty, University of Muhammadiyah Metro). The type of research was quantitative with a population of 1,107 students who are active at Muhammadiyah Metro University class of 2019-2022. In accordance with the slovin formula, the sample used was 92 students. Data collection methods used were observation and questionnaires. Data analysis were undergone by testing instrument requirements, testing analysis for regression, and testing hypotheses. Based on the results of the T test found that income expectations had no positive and insignificant effect on the interest in entrepreneurship in students of the Economics and Business Faculty at Muhammadiyah University of Metro, family environment had a positive and significant effect on interest in entrepreneurship on students of the Economics and Business Faculty, Muhammadiyah University of Metro and entrepreneurship education had a positive effect and significant to the interest in entrepreneurship in students of the Economics and Business Faculty, University of Muhammadiyah Metro. From the F test was found that income expectations, family environment and entrepreneurship education had a significant effect on the interest in entrepreneurship in students of the Economics and Business Faculty, Muhammadiyah University of Metro.